2011
DOI: 10.1007/s00280-011-1561-8
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic model in patients who receive chemotherapy for metastatic or recurrent gastric cancer: validation and comparison with previous models

Abstract: Validation and comparison of prognostic models indicated that our model was as effective as the previous models to stratify the patients with AGC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 34 publications
1
63
1
2
Order By: Relevance
“…Overall, 3494 patients (89.9 %) died, with a median OS of 10.6 months (95 % CI 10.2-11.0). The median followup time for living patients was 25.2 months [interquartile According to our previous prognostic model using eight prognostic factors (mentioned previously) [14], the patients were grouped into three groups. In the good risk group, the OS showed statistically significant improvement over the study period: 12.3 months (95 % CI 11.0-13.6) in period 1, 13.0 months (95 % CI 11.8-14.1) in period 2 and 15.8 months (95 % CI 14.9-16.7 months) in period 3 (p for trend = 0.002, Fig.…”
Section: Betweenmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 3494 patients (89.9 %) died, with a median OS of 10.6 months (95 % CI 10.2-11.0). The median followup time for living patients was 25.2 months [interquartile According to our previous prognostic model using eight prognostic factors (mentioned previously) [14], the patients were grouped into three groups. In the good risk group, the OS showed statistically significant improvement over the study period: 12.3 months (95 % CI 11.0-13.6) in period 1, 13.0 months (95 % CI 11.8-14.1) in period 2 and 15.8 months (95 % CI 14.9-16.7 months) in period 3 (p for trend = 0.002, Fig.…”
Section: Betweenmentioning
confidence: 99%
“…Patients' medical records, stored in a prospectively collected registry, were reviewed for information regarding demographic data, tumor characteristics, treatment types, treatment responses and survival. In addition, patients were grouped by our prognostic model for MRGC [14]. This model used a scoring system consisting of eight prognostic factors [Eastern Cooperative Oncology Group (ECOG) performance score (PS) C2 or bone metastasis (2 points each); no gastrectomy, peritoneal metastasis, lung metastasis, alkaline phosphatase [120 IU/ l, albumin \3.3 g/dl or total bilirubin [1.2 mg/dl (1 point each)], with patients divided into good (0-1 points), moderate (2-3) and poor (C4) risk groups.…”
Section: Patients and Data Collectionmentioning
confidence: 99%
“…It is essential to distinguish the nature of recurrent gastric cancer by the occurrence of symptoms and evaluation the risk factors for planning further treatment (Kim et al, 2010). Validation and comparison of prognostic factors will indicate the effective models to predict the patterns of recurrence (Koo et al, 2011). Although several studies have been published on prognostic risk factors generally used in clinical practice for gastric cancer, the patterns of recurrence are still under debate in different societies.…”
Section: Introductionmentioning
confidence: 99%
“…To select the most optimal of our five candidate models, three of the four factors (PS $1, number of metastatic sites $2, and no prior gastrectomy), excluding elevated ALP and LDH, were included in all models, and we selected elevated ALP from the point of consistency in previous reports [14,15,17]. Both LDH and ALP commonly represent liver function, bone metastasis, and other abnormal conditions; however, there were no previous reports of prognostic models, including LDH.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a few reports have described prognostic factors for GC from Korean patients [15][16][17]. Lee et al [15] reported ECOG PS $2, no prior gastrectomy, peritoneal metastasis, bone metastasis, elevated ALP, and decreased albumin as independent prognostic factors; Kim et al [16] reported ECOG PS $2, peritoneal metastasis, bone metastasis, metastatic sites $2, and elevated total bilirubin as prognostic factors; and Koo et al [17] reported ECOG PS $2, no prior gastrectomy, peritoneal metastasis, bone metastasis, lung metastasis, elevated ALP, decreased albumin, and elevated total bilirubin as prognostic factors. Only PS was a common prognostic factor in all four studies, and peritoneal and bone metastasis were shared among three studies.…”
Section: Discussionmentioning
confidence: 99%